A Greener Protocol for Accessing 2,3-Dihydro/spiroquinazolin-4(1H)-ones: Natural Acid-SDS Catalyzed Three-Component Reaction - Sharma, Rashmi; Pandey, Anand Kumar; Chauhan, Prem M. S. (Synlett, 2012)
A novel green and energy-efficient synthesis of 2,3-dihydro/spiroquinazolin-4(1H)-ones via three-component cyclocondensation reaction involving isatoic anhydride, amines and aldehydes/ketones utilizing recyclable tartaric acid–SDS catalyst system has been achieved. With simple requirements of mechanical stirring or mechanochemical activation at room temperature and one of the shortest reported times as of yet, it is a significant improvement on previously described methods for the synthesis of such compounds. Moreover the catalyst system can also be efficiently applied in large-scale reactions which indicates the potential for applications in industry.
Keywords: 2,3-dihydroquinazolin-4(1H)-one; mechanochemical activation; multicomponent reaction; sodium dodecyl sulfate (SDS); tartaric acid